2014
DOI: 10.1097/bot.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Outcome and Patient-Reported Function After Intramedullary Nailing

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 41 publications
3
100
0
Order By: Relevance
“…Since then there have been multiple reports of functional outcomes following intramedullary fixation of tibia fractures 33,34 , however cohorts have often been small and assessments were limited to questions regarding knee pain or activity and employment 35,36 . Court-Brown et al, evaluated the functional recovery of 100 patients with closed tibia fractures who were enrolled in a prospective trial of reamed versus unreamed tibial nails and found that the average time to return to work and jumping activities was approximately 11 weeks, though they did not report the proportion of those who had returned to full activity at one year.…”
Section: Discussionmentioning
confidence: 99%
“…Since then there have been multiple reports of functional outcomes following intramedullary fixation of tibia fractures 33,34 , however cohorts have often been small and assessments were limited to questions regarding knee pain or activity and employment 35,36 . Court-Brown et al, evaluated the functional recovery of 100 patients with closed tibia fractures who were enrolled in a prospective trial of reamed versus unreamed tibial nails and found that the average time to return to work and jumping activities was approximately 11 weeks, though they did not report the proportion of those who had returned to full activity at one year.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if suprapatellar intramedullary nailing has a lower incidence of knee pain after stabilization of a tibia fracture with an intramedullary rod versus an infrapatellar approach. A retrospective analysis of consecutive patients treated with either a suprapatellar approach or an infrapatellar approach was completed by Jones et al 24 . No differences were seen in knee pain score using the Kujala score as measure of anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore Jones et al showed significantly better reductions and more accurate starting points in the suprapatellar approach. 10 Concluding that the suprapatellar approach offers facilitated reduction in particular in proximal third tibia fractures, decreased postoperative anterior knee pain, excellent tibial alignment and union. Caregivers may remain reluctant to implement this novel, innovative technique due to concerns regarding iatrogenic damage to the patellofemoral joint especially in young patients.…”
Section: Discussionmentioning
confidence: 99%